101 proposals to reform the stability adn growth pact. : why so many? A survey - Fischer, Jonas; Jonung, Lars.; Larch, Martin; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2006)
The failure of key EU Member States to respect the requirements of the Stability and Growth Pact (SGP) a few years after its inception triggered a heated debate on how to reform the framework of fiscal policy coordination in the Economic and Monetary Union (EMU). This paper systematically analyzes 101 reform proposals presented by professional academic and non-academic economists prior to March 2005, when the Council of the European Union adopted a revised version of the SGP. Each proposal is characterized by a set of variables reflecting features such as the degree of modification of the SGP, the background of its author(s), the main aim attached to fiscal policy coordination in the EMU, the timing of the proposal and the type of proposal made. Using multivariate statistical analysis, roughly four different schools of thought concerning the reform of the SGP are identified. In line with the main findings of the political economy literature, all four schools of thought share the view that in the absence of specific rules fiscal policy would lead to excessive deficits and hence affect the conduct of the common monetary policy. However, beyond this common denominator, there is no consensus on how best to co-ordinate fiscal policy. Several explanations for the multitude of proposals are presented, the most important being the present lack of a consensus in the economics profession concerning the role of fiscal policy.
Economic Papers